Serious maternal complications in relation to severe pre‐eclampsia: a retrospective cohort study of the impact of hospital volume. (21st October 2016) - Ananth, CV; Lavery, JA; Friedman, AM; Wapner, RJ; Wright, JD
Abstract : Objective: We examined rates of serious maternal complications in relation to severe pre‐eclampsia based on the delivering hospital's annualised volume. Design: Retrospective cohort study. Population and setting: Singleton deliveries ( n = 25 782 235) in 439 hospitals in the USA. Methods: Annualised hospital volume was categorised as 25–500, 501–1000, 1001–2000 and >2000. Main outcome measures: Rates of in‐hospital maternal death and serious maternal complications, including puerperal cerebrovascular disorders, pulmonary oedema, disseminated intravascular coagulation, acute renal, heart and liver failure, sepsis, haemorrhage and intubation in relation to severe pre‐eclampsia. We derived adjusted risk ratio (RR) and 95% confidence interval (CI), from hierarchical Poisson regression models. Results: Severe pre‐eclampsia was associated with an 8.7‐fold (95% CI 7.6, 10.1) risk of composite maternal complications, with similar RRs across levels of hospital volumes. However, compared with hospitals with low annual volume (<2000), maternal mortality rates in relation to severe pre‐eclampsia were lower in high volume hospitals. The rates of serious maternal complications were 410.7 per 10 000 to women who delivered in hospitals with a high rate of severe pre‐eclampsia (≥2.12%) and 584.8 per 10 000 to women who delivered in hospitals with low severe pre‐eclampsia rates (≤0.41; RR 1.75, 95% CI 1.24, 2.45). Conclusions: While the risks of serious maternal complications in relation to severe pre‐eclampsia was similar across hospital delivery volume categories, deaths showed lower rates in large delivery volume hospitals than in smaller volume hospitals. The risk of complications was increased in hospitals with low compared with high severe pre‐eclampsia rates. Tweetable abstract: Hospital volume had little impact on the association between severe pre‐eclampsia and maternal complications. Abstract : Tweetable abstract Hospital volume had little impact on the association between severe pre‐eclampsia and maternal complications.